PELAKSANAAN PROGRAM KESEHATAN DAN KESELAMATAN KERJA DI LINGKUNGAN KERJA GUNA MENINGKATKAN PRODUKTIVITAS KERJA - Mulyapradana, Aria; Kharis, Aghus Jamaludin; Muafiq, Farikhul; Asyarotun; Kamilia, Nurul (Jurnal Bina Akuntansi, 2025)
The aim of this research is to determine whether the implementation of occupational health and safety programs in the work environment can increase employee work productivity. The method used was a qualitative descriptive approach with 4 informants from UMKM Jie Food Sejahtera consisting of 1 business owner and 3 employees in the production section. Data collection techniques use interviews, observation and literature studies. The results of the research are that MSME Jie Food Sejahtera has implemented the K3 program in the work environment quite well, this has an impact on employees feeling safe and comfortable at work so that work productivity increases. There are several things that business owners need to pay attention to, including providing regular K3 training, updating work instructions, increasing employee awareness of using PPE while working